Interaction of huntingtin with PRMTs and its subsequent arginine methylation affects HTT solubility, phase transition behavior and neuronal toxicity. Issue 10 (9th December 2021) - Ratovitski, Tamara; Jiang, Mali; O'Meally, Robert N; Rauniyar, Priyanka; Chighladze, Ekaterine; Faragó, Anikó; Kamath, Siddhi V; Jin, Jing; Shevelkin, Alexey V; Cole, Robert N; Ross, Christopher A
Abstract: Huntington's disease (HD) is an incurable neurodegenerative disorder caused by a CAG expansion in the huntingtin gene ( HTT ). Post-translational modifications of huntingtin protein (HTT), such as phosphorylation, acetylation and ubiquitination, have been implicated in HD pathogenesis. Arginine methylation/dimethylation is an important modification with an emerging role in neurodegeneration; however, arginine methylation of HTT remains largely unexplored. Here we report nearly two dozen novel arginine methylation/dimethylation sites on the endogenous HTT from human and mouse brain and human cells suggested by mass spectrometry with data-dependent acquisition. Targeted quantitative mass spectrometry identified differential arginine methylation at specific sites in HD patient-derived striatal precursor cell lines compared to normal controls. We found that HTT can interact with several type I protein arginine methyltransferases (PRMTs) via its N-terminal domain. Using a combination of in vitro methylation and cell-based experiments, we identified PRMT4 (CARM1) and PRMT6 as major enzymes methylating HTT at specific arginines. Alterations of these methylation sites had a profound effect on biochemical properties of HTT rendering it less soluble in cells and affected its liquid–liquid phase separation and phase transition patterns in vitro. We found that expanded HTT 1-586 fragment can form liquid-like assemblies, which converted into solid-like assemblies when the R200/205 methylation sites were altered. Methyl-null alterations increased HTT toxicity to neuronal cells, while overexpression of PRMT 4 and 6 was beneficial for neuronal survival. Thus, arginine methylation pathways that involve specific HTT-modifying PRMT enzymes and modulate HTT biochemical and toxic properties could provide targets for HD-modifying therapies.